PENGARUH TAX HAVEN, FOREIGN OWNERSHIP DAN EXCHANGE RATE TERHADAP TRANSFER PRICING - M. Irvan Muhsin; Abidin, Jaenal (Jurnal Nusa Akuntansi, 2025)
This study aims to analyze and prove empirically the effect of Tax Haven, Foreign Ownership, and Exchange Rate  on Transfer Pricing. This type of research is associative quantitative using secondary data taken from the Indonesia Stock Exchange's website, the company's website. The population in this study were  minimg sector companies listed on the Indonesia Stock Exchange for the period 2018 – 2022. The sample selection procedure in this study used purposive sampling, and only 12 companies met the criteria with a 5 year research period. So that as many as 60 data were obtained as samples in this study. The data analysis technique used is panel data regression analysis using E- views 12 version. The results of this study indicate that partially Tax Haven has an effect on Transfer Pricing, Foreign Ownership has no effect on Transfer Pricing, and Exchange Rate has no effect on Transfer Pricing. Simultaneously Tax Haven, Foreign Ownership, and Exchange Rate affect Transfer Pricing.